Cereal market in Romania-regional competitiveness - Dan-Marius Voicilaş (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 5th Edition of the International Symposium, November 2014, Bucharest, 2014)
The article analyses the Romanian cereal sector in the last decades. The analysis gives a special attention to the sector development level and its evolution by regions. We analyze areas, productions, yields and the trade with cereals, at national and regional level. We try to identify how competitive the sector is and the main factors of influence, based on some quantitative indicators. Moreover, we identify the negative factors which influenced it. The statistical analysis is based on long data series and concentrates on the years before and after Romania's accession into EU. We use data provided by the National Institute of Statistics. The results presented show the evolution of the cereal sector after 1989, its decline for about ten years, but also the recovery, especially after the EU accession. The article opens new discussions about the role of the cereal sector in the Romanian economy and the ways of development in the context of a high level of competitiveness among European Union countries and other countries in the world. At the same time, by the present analysis we want to show how the regional performances can contribute to the development of the cereal market in Romania.
Keywords: 330; cereals; regions; competitiveness; Romania